Strategic Foundations of Rational Expectations - Barelli, Paulo,Govindan, Srihari,Wilson, Robert (SSRN, 2022)
We study an economy with traders whose payoffs are quasilinear and their private signals are informative about an unobserved state parameter. The limit economy has infinitely many traders partitioned into a finite set of symmetry classes called types. It has a unique rational expectations Walrasian equilibrium (REE) whose price reveals the state. Total monotonicity, a property that limits heterogeneity across types, determines whether an efficient social choice function (SCF) is attainable using mechanisms in a class that includes auctions. An average crossing property on the primitives is a sufficient condition for total monotonicity. The REE is an efficient SCF so it is attainable by an auction if and only if it satisfies total monotonicity. REE with total monotonicityis not only attainable, but also implementable: it is approximated by the equilibrium outcomes of auctions with finitely many traders of each type and fine grids of the state, signals and bids
10.2139/ssrn.4217113
Keywords: Arbeitspapier; Graue Literatur; auctions; double auctions; equilibria; rational expectations; information aggregation